Penerapan Model Pembelajaran Kooperatif Metode Course Review Horay untuk Meningkatkan Aktivitas dan Prestasi Belajar Siswa - Samsul Bahri; Farah Heniati Santosa (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2021)
This study aims to improve the activity and learning achievement of students of class VII F SMP Negeri 15 Mataram by applying for the Course Review Horay learning method. This research is a classroom action research conducted in three cycles, and each cycle consists of five stages, namely the planning, action, observation, evaluation, and reflection stages. The results showed that there was an increase in activity and student learning achievement from cycle to cycle. The average value of student learning achievement for the first cycle, second cycle, and third cycle is 72,60; 83,87 and 86,30. The classical completeness in succession achieved is 74,91%; 83,87% and 93,54%. While the average score of student activity in cycle I, cycle II, and cycle III was 8.67 with quite active activity criteria, 10.5 with active activity criteria, and 12.5 with activity criteria very active. By paying attention to the results and work indicators that are achieved, it can be concluded that the application of cooperative learning models with the Course Review Horay method can increase the activity and learning achievement of students of class VII F of SMP Negeri 15 Mataram.